PELATIHAN PIJAT OKETANI DI PMB WAHYUNI: PIJAT OKETANI - Azizati Salmas Marsiami; Wahyu Widayati; Wahyu Dwi Fatimah (Educativo: Jurnal Pendidikan, 2022)
Exclusive breastfeeding has many benefits for both mother and baby. Postpartum mothers, especially days 1-7 postpartum, have various problems in breastfeeding, such as breast swelling which causes breast pain to breast abscess. The solution that can be given is oketani massage. Oketani massage is a breast treatment that can be done manually by the attachment between the base of the breast and the pectoralis major fascia. Oketani massage helps restore normal breast function, namely areola and nipples are more elastic so that the baby can suck milk more easily. Oketani massage solves the baby's problem of not getting enough milk or sore nipples, breast swelling and mastitis. The implementation method is the lecture method, question and answer/discussion and demonstrations. After the implementation is carried out, immediately provide breast care with Oketani massage therapy for postpartum women for 30-40 minutes in the morning and pain within 3 days. The results obtained are oketani massage which can reduce breast pain in postpartum mothers, increase milk production, and make the breasts feel more comfortable. In infants, the results obtained are the frequency of breastfeeding more often and the baby sleeps better.